RANCANGAN BUKU SAKU KEANEKARAGAMAN MAKROFUNGI PADA MATERI FUNGI KELAS X SMA - Zatri Rahayu; Irda Sayuti; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of the pocket book design of macrofungi diversity on fungi material grade X Biology learning. This research was conducted at the Bina Widya Campus, Riau University in January - April 2021. The design of this pocket book refers to the ADDIE development model, the stage used is only the analysis and design stage. The analysis stage was carried out by analyzing the 2013 curriculum and analyzing the learning material. The design stage is carried out by designing the syllabus and lesson plans first, then designing a pocket book. This type of study is qualitative descriptive and the research method used is survey method combined with the squares method. Based on the potential analysis, was found 36 species of macroscopic fungi from 21 families and 9 orders that could be used as a pocket book design for macrofungi diversity for learning media on Fungi material for high school grade X KD 3.7.Key Words: Pocket Book, Learning Media, Macrofungi